Emotional intelligence as panacea for socio-political challenges (2013)
This paper examined the effect of emotional intelligence as a counselling tool for reducing socio-political challenges among political leaders. In doing this, the factors affecting good governance were analysed and recommendations were made to help remedy the Problems.